PROCESSES OF RADICAL CHANGE IN THE DEVELOPMENT OF CIVIL SOCIETY IN NEW UZBEKISTAN - Masharipov Ikramjon Batirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article analyzes the fundamental political, legal, and institutional reforms being implemented in the processes of forming and developing civil society in New Uzbekistan. The author studied the activities of civil society institutions, mahallas, non-governmental non-profit organizations, mass media, and political parties within the framework of the New Uzbekistan concept and highlighted their role in ensuring human rights and freedoms, increasing the social activity of youth and women.